1994
DOI: 10.1159/000262016
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Inhibits the Antimicrobial Peroxidase Systems in Human Whole Saliva

Abstract: Fluoride (F-) ions at concentrations present in vivo at the plaque/enamel interface (0.05–10 mM) inhibited the 4activities of lactoperoxidase (LP), myeloperoxidase (MP) and total salivary peroxidase (TSP) in a pH- and dose-dependent way. The inhibition was observed only at pH ≤ 6.5 and with F concentrations ≥ 0.1 mM. At pH 5.5 LP activity was inhibited by 85% and MP by 34% with 10 mM F-. TSP activity was also inhibited only at low pH (5.5) by approximately 25%. Furthermore, the generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…It is noteworthy that SPO was found to have lower pH optima relative to LPO, but it also was inhibited by F -at sufficiently low pH (Thibodeau et al, 1985). A similar inhibitory effect of F -on peroxidase activity has been observed in whole saliva (Thibodeau et al, 1985;Hannuksela et al, 1994;van den Abbeele et al, 1995). These observations suggest that F -in dental plaque may inhibit the peroxidase defense system.…”
Section: Fluoridementioning
confidence: 57%
“…It is noteworthy that SPO was found to have lower pH optima relative to LPO, but it also was inhibited by F -at sufficiently low pH (Thibodeau et al, 1985). A similar inhibitory effect of F -on peroxidase activity has been observed in whole saliva (Thibodeau et al, 1985;Hannuksela et al, 1994;van den Abbeele et al, 1995). These observations suggest that F -in dental plaque may inhibit the peroxidase defense system.…”
Section: Fluoridementioning
confidence: 57%
“…Some years ago, Thibodeau et al ( 18) found that under acid conditions, such as those in dental plaque, fluoride is inhibitory for lactoperoxidase and salivary peroxidases. These findings have subsequently been confirmed and extended ( 9, 21). Thibodeau & Keefe ( 19) showed also that fluoride could inhibit the heme catalase of A. viscosus under acid conditions but found only minor enhancement by fluoride of peroxide killing of the organism.…”
supporting
confidence: 53%
“…Therefore, fluoride inhibition of peroxidases is not likely to be very important in saliva but could be important in plaque where acidification occurs regularly, especially in cariogenic plaque in which fluoride is concentrated. van den Abbeele et al (1992) and Hannuksela et al (1994) more recently reinvestigated the inhibitory effects of fluoride on salivary peroxidases with an orientation to fluoride acting to inhibit the known antimicrobial actions of the enzymes, especially in conjunction with thiocyanate, which is abundant in saliva.…”
Section: Catalasementioning
confidence: 99%